2021
DOI: 10.3390/jcm10153413
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF-α (-308G/A) Gene Polymorphism with Circulating TNF-α Levels and Excessive Daytime Sleepiness in Adults with Coronary Artery Disease and Concomitant Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) is common in patients with coronary artery disease (CAD), in which inflammatory activity has a crucial role. The manifestation of OSA varies significantly between individuals in clinical cohorts; not all adults with OSA demonstrate the same set of symptoms; i.e., excessive daytime sleepiness (EDS) and/or increased levels of inflammatory biomarkers. The further exploration of the molecular basis of these differences is therefore essential for a better understanding of the OSA pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…As previously described in detail [ 35 ], genomic DNA was isolated from whole blood samples collected in EDTA-coated tubes using the PAXgene Blood DNA Kit (PreAnalytiX; Qiagen). The quality and concentration of DNA samples were determined using a nanodrop photometer (NanoDrop 2000; Thermo Scientific, Waltham, MA, USA), and DNA samples were stored at −80 degrees.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described in detail [ 35 ], genomic DNA was isolated from whole blood samples collected in EDTA-coated tubes using the PAXgene Blood DNA Kit (PreAnalytiX; Qiagen). The quality and concentration of DNA samples were determined using a nanodrop photometer (NanoDrop 2000; Thermo Scientific, Waltham, MA, USA), and DNA samples were stored at −80 degrees.…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that patients with CAD and OSA carrying the TNF-α A allele had increased circulating TNF-α levels compared with the ones carrying the TNF-α G allele [ 35 ] in the “Randomized Intervention with CPAP in CAD and OSA” (RICCADSA) cohort [ 36 ]. In the current study, we addressed the role of TNF-α (-308G/A) gene polymorphism on circulating TNF-α levels in response to 12 months of CPAP therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors including environmental and genetic factors, and even internal conditions (hormones, cytokines, and other biomarkers), might lead to the emergence and maintenance of OSA. Smoking [ 12 ] and alcohol consumption [ 13 ], and alterations in the blood levels of intercellular adhesion molecule-1 [ 14 ], monocyte chemoattractant protein-1 [ 15 ], adiponectin [ 16 ], C-reactive protein [ 17 ], cortisol [ 18 ], interleukin-6 [ 19 ], tumor necrosis factor-alpha [ 20 ], astrocytic protein (S100B) [ 21 ], neuron-specific enolase [ 21 ], and polymorphisms [ 22 , 23 , 24 ] were observed among adults with OSA, compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…OSA patients have a high risk of secondary cardiovascular diseases (CVDs), especially abnormalities in left ventricular geometry (LVG), which is an influential factor in the prognosis and treatment complexity of OSA 3,4 . Repeated IH/R leads to an increase in free radical concentration in OSA patients, which leads to increased pro‐inflammatory cytokine activity, including tumor necrosis factor‐α (TNF‐α), thereby inducing a systemic inflammatory response 5 . In addition, an increase in TNF‐α concentrations in serum is considered a risk factor for CVDs, 6 and myocardial cell‐specific expressed TNF‐α is linked to left ventricular remodeling 7 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Repeated IH/R leads to an increase in free radical concentration in OSA patients, which leads to increased pro-inflammatory cytokine activity, including tumor necrosis factor-α (TNF-α), thereby inducing a systemic inflammatory response. 5 In addition, an increase in TNF-α concentrations in serum is considered a risk factor for CVDs, 6 and myocardial cell-specific expressed TNF-α is linked to left ventricular remodeling. 7 There is an increasing amount of evidence indicating that genetic factors are in part engaged in the occurrence of OSA.…”
mentioning
confidence: 99%